TRAVEL GROWTH ANALYSIS OF ACTIVITY SYSTEMS FOR THE NEED FOR A MASS TRANSPORT SYSTEM IN SERANG CENTER - Annisa Nurjanah; Juang Akbardin; Odih Supratman (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2022)
Serang City is preparing for the development of infrastructure and road network, so that every area in Serang City can be well integrated. Serang City has 6 sub-districts, including the center of national activities and is a big city because it has a population of around 652,192 people (BPS, 2019). By knowing the growth of the LHRT, the generation and attraction models of movement in the city center, based on the direction of the zone under review, namely north, west, east and south in the internal zone of Serang City and the external zone around Serang City. With the multiple regression analysis method on the generation and attraction models of movement which are analyzed based on socio, economic and demographic variables with dominant factors. The independent variables measured were population (X1), number of health facilities (X2), number of schools (X3), number of workers (X4), GRDP (X5) and the dependent variable is the amount of daily average annual traffic (Y). The results of the equations of motion obtained are 4 generation equations, 4 pull equations and the value of the determinant of each equation.